Trimethylamine N‐Oxide Promotes Vascular Inflammation Through Signaling of Mitogen‐Activated Protein Kinase and Nuclear Factor‐κB. Issue 2 (22nd February 2016) - Seldin, Marcus M.; Meng, Yonghong; Qi, Hongxiu; Zhu, WeiFei; Wang, Zeneng; Hazen, Stanley L.; Lusis, Aldons J.; Shih, Diana M.
Abstract : Background: The choline‐derived metabolite trimethylamine N‐oxide (TMAO) has been demonstrated to contribute to atherosclerosis and is associated with coronary artery disease risk. Methods and Results: We explored the impact of TMAO on endothelial and smooth muscle cell function in vivo, focusing on disease‐relevant outcomes for atherogenesis. Initially, we observed that aortas of LDLR −/− mice fed a choline diet showed elevated inflammatory gene expression compared with controls. Acute TMAO injection at physiological levels was sufficient to induce the same inflammatory markers and activate the well‐known mitogen‐activated protein kinase, extracellular signal–related kinase, and nuclear factor‐κB signaling cascade. These observations were recapitulated in primary human aortic endothelial cells and vascular smooth muscle cells. We also found that TMAO promotes recruitment of activated leukocytes to endothelial cells. Through pharmacological inhibition, we further showed that activation of nuclear factor‐κB signaling was necessary for TMAO to induce inflammatory gene expression in both of these relevant cell types as well as endothelial cell adhesion of leukocytes. Conclusions: Our results suggest a likely contributory mechanism for TMAO‐dependent enhancement in atherosclerosis and cardiovascular risks.